Checklist of sponges (Porifera) from the White Sea, Arctic - Ereskovsky, Alexander; Morozov, Grigori (Zootaxa, 2025)
A checklist of the sponge fauna from the White Sea, Russia was compiled from published literature. This study provides a partial update to the “Checklist of sponges (Porifera) of the White Sea” published about 30 years ago. A total of 86 sponge species distributed among two classes of Porifera, Demospongiae and Calcarea, were identified in the White Sea. 18 of them are endemic to the White Sea. They belong to three subclasses and 10 orders of Demospongiae and two subclasses and two orders of Calcarea. In this paper we also give a brief overview of biogeography, vertical distribution and substrate preferences of the White Sea sponges.